Analisis Pengaruh Lingkungan Keluarga dalam Pembentukan Karakter Siswa SDN Kampung Batas Desa Sukajaya - Dwi Meta Febriyanti (TEKNO AULAMA: Jurnal Teknologi Pendidikan Islam, 2026)
This study, titled “An Analysis of the Influence of the Family Environment on the Character Formation of Students at SD Negeri Kampung Batas, Sukajaya Village, Bayung Lencir District, Musi Banyuasin Regency,” aims to examine how the family environment shapes students’ character and to assess the extent to which the family contributes to instilling character values in elementary school–aged children. A descriptive quantitative approach was employed, with data collected through questionnaires, observations, and documentation. The study involved a population of 152 students, from which 39 second-grade students were selected using purposive sampling. Data analysis was conducted using SPSS through several statistical tests, including validity, reliability, normality, simple regression, and partial t-tests. The results indicate that the family environment has a significant influence on students’ character formation. Parenting styles, the quality of communication at home, and parental role modeling play essential roles in shaping children’s fundamental behavior. At school, character development is reflected in students’ discipline, responsibility, social interaction skills, and adherence to rules. Statistically, the influence of the family environment is significant, with a p-value of 0.041 (p < 0.05) and a regression coefficient of β = 0.329, demonstrating that a more supportive family environment corresponds to more positive character development. In conclusion, the family serves as the primary and most influential factor in shaping the character of elementary school students. Therefore, continuous collaboration between parents and schools is necessary to ensure optimal character development.